The novel c-Met inhibitor cabozantinib overcomes gemcitabine resistance and stem cell signaling in pancreatic cancer - Hage, Carina; Giese, Nathalia; Giese, Thomas; Schönsiegel, Frank; Nwaeburu, Clifford C.; Herr, Ingrid (Cell death & disease, 2013)
Pancreatic ductal adenocarcinoma (PDA) is one of the most lethal malignancies. Cancer stem cells (CSCs), which are not targeted by current therapies, may be the reason for pronounced therapy resistance. A new treatment option in phase II trials is cabozantinib that inhibits the pancreatic CSC surface marker and tyrosine kinase receptor c-Met. The purpose of this study was to evaluate the effect of cabozantinib to stem-like features and therapy resistance. Established PDA cell lines, a gemcitabine-resistant subclone, non-malignant pancreatic ductal cells and primary spheroidal cultures from patient tumors were analyzed by MTT-assay, flow cytometry, colony and spheroid formation assays, western blotting, qRT-PCR, antibody protein array, immunohistochemistry and morphological features. Cabozantinib inhibited viability and spheroid formation and induced apoptosis in malignant cells with minor effects in non-malignant cells. After long-term cabozantinib treatment, PDA cells had altered anti- and pro-apoptotic signaling, but still responded to cabozantinib, as apoptosis only slightly decreased and viability only slightly increased suggesting a low resistance-inducing potential of cabozantinib. In parallel, c-Met expression and the pluripotency transcription factor SOX2 were downregulated, which might counteract development of full therapy resistance in long-term treated subclones. In single-treatment studies, cabozantinib increased efficacy of gemcitabine. Most importantly, cabozantinib strongly induced apoptosis and reduced viability in PDA cell lines, which are completely resistant toward gemcitabine. In primary, CSC-enriched spheroidal cultures cabozantinib downregulated CSC markers SOX2, c-Met and CD133 and induced apoptosis. These findings suggest that the clinical use of cabozantinib may be more effective than current chemotherapeutics.
Gesehen am 19.10.2021